Primary porcine fibroblasts: Ochratoxin A cytotoxicity and role of all-trans-retinol and alpha-tocopherol - A. Baldi; K. Sejrsen; S. Purup; L. Sangalli; R. Rebucci; E. Fusi (Italian Journal of Animal Science, 2010)
Ochratoxin A (OTA) is a mycotoxin produced by Aspergillus and Penicillium species and it is a contaminant of food and feeds (O’Brien et al., 2001). OTA is a nephrotoxic, carcinogenic and teratogenic compound and one of the most sensible species among domestic animals is the pig (JECFA, 2001). Production of free radicals or reactive oxygen species (ROS) leading to lipid peroxidation was suggested to be one of the mechanisms by which OTA damages the cell (Rahimtula et al., 1988).